Attention Restoration Theory: Exploring the Role of Soft Fascination and Mental Bandwidth. Issue 9 (November 2019) - Basu, Avik; Duvall, Jason; Kaplan, Rachel
Soft fascination is a key but underexamined element of Attention Restoration Theory (ART). According to ART, attending to softly fascinating stimuli not only requires little effort but also leaves mental space for reflection. We propose that soft fascination can be characterized as the interaction of both attentional effort and mental bandwidth and hypothesize that the restorative potential of everyday activities can be categorized based on this interaction. In an online survey, 398 adults rated four activities on Mental Bandwidth (MB), Perceived Restorativeness (PR), and preference. Supporting the hypothesis, the results showed that walking in nature was perceived as softly fascinating, whereas watching television was a source of hard fascination. Furthermore, PR, but not MB, was highly correlated with preference. Findings are discussed in the context of developing a measure to help people better anticipate activities that may or may not be restorative.